2016
DOI: 10.1016/j.yqres.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Chironomids as indicators of natural and human impacts in a 700-yr record from the northern Patagonian Andes

Abstract: Chironomid communities were studied in a sediment core collected from Lake Moreno Oeste, located in Nahuel Huapi National Park. A major change in midge assemblages occurred at ∼AD 1760, which was characterized by a decrease of “cold taxa” including Polypedilum sp.2 and Dicrotendipes, and an increase of “warm taxa” including Apsectrotanypus and Polypedilum sp.1. These taxa are likely related to climatic conditions concurrent with the end of a cold period at ∼AD 1500-1700 and the beginning of a drying climate at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 47 publications
5
22
1
Order By: Relevance
“…This study agrees with previous studies carried out in lakes of northern Patagonia, which evaluated the effect of recent eruption of these events on lake productivity (Modenutti et al 2013;Balseiro et al 2014) and on the mechanical impact of the ash deposition on chironomid communities (Massaferro et al 2005;Araneda et al 2007;Serra et al 2016, Williams et al 2016). However, rising temperatures of the last 50 years, and the increase in human activities also caused environmental changes that enhanced lake productivity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study agrees with previous studies carried out in lakes of northern Patagonia, which evaluated the effect of recent eruption of these events on lake productivity (Modenutti et al 2013;Balseiro et al 2014) and on the mechanical impact of the ash deposition on chironomid communities (Massaferro et al 2005;Araneda et al 2007;Serra et al 2016, Williams et al 2016). However, rising temperatures of the last 50 years, and the increase in human activities also caused environmental changes that enhanced lake productivity.…”
Section: Discussionsupporting
confidence: 92%
“…Tephra layers were not incorporated into the model but were used as additional data to verify the robustness of the age model. Previous tephrocronological studies in the area helped to identify volcanic eruptions responsible for ash deposition in both lakes during the last 200 years (Daga et al 2006Bertrand et al 2008Bertrand et al , 2014Ribeiro Guevara et al 2010;Fontijn et al 2014;Serra et al 2016, Williams et al 2016). …”
Section: Chronologiesmentioning
confidence: 99%
“…Such records are particularly important for remote mountain regions where long-term records are otherwise unavailable and provide insights into regional variations of global warming. Sub-fossils of chironomids, which are particularly sensitive to temperature changes, have been used to infer past air temperatures and show that in many mountain regions temperatures have increased rapidly over the last century (Battarbee et al, 2002;Solovieva et al, 2005;Reinemann et al, 2014b;Williams et al, 2016;Porinchu et al, 2017). In the southern mountains of Costa Rica, sub-fossil chironomids quantified late-Holocene thermal variability including evidence for the Little Ice Age as well as changes in lake level caused by drought (Wu et al, 2017).…”
Section: Paleolimnological Records Provide Insight Into Global Climatmentioning
confidence: 99%
“…Previous research has shown that the main changes in chironomid assemblages in lacustrine environments in Patagonia have been due to changes in the climatic conditions of the region. For example, in Lake Moreno Oeste (northern Patagonia), the main change in the chironomid community in the past 700 years was associated with the end of the cold period (~AD 1500–1700) and the beginning of the dry period (~AD 1740–1900; Williams et al, 2016).…”
Section: Introductionmentioning
confidence: 99%